A „visszatért" területek katonai közigazgatása (1938-1941) - Suba, János (Közép-Európai Közlemények, 2013)
The task of the Hungarian leaders were the returned region’s integrations a smart pace to a life of the state. Leader of the Hungarian paramilitary administration was the Chief of General Staff, he worked by the Guidelines of National Defense Council. Central organization was the quartermaster group. This group has a „principle”, „civil” and „armaments industry” departement. The „principle departement” made a preparations of measure and leaded the produce of rule. The quartermaster group’s published the orders of administrations. In this departement were some civil expert, they worked at administration. The military leader personalization the low of the civil authority. The east territory’s and Transylvanian country’s paramilitary administration has a tree part: „Town (district) HQ”, „Country military HQ” and the „Departement of Army’s paramilitary group”. These in the south region were only two class: „Town (district) HQ” and „Departement of Army’s paramilitary group”.